A review of bioactive glasses: Their structure, properties, fabrication and apatite formation. Issue 1 (7th May 2013) - Kaur, Gurbinder; Pandey, O.P.; Singh, K.; Homa, Dan; Scott, Brian; Pickrell, Gary
<x xml:space="preserve">Abstract</x> Bioactive glass and glass–ceramics are used in bone repair applications and are being developed for tissue engineering applications. Bioactive glasses/Bioglass are very attractive materials for producing scaffolds devoted to bone regeneration due to their versatile properties, which can be properly designed depending on their composition. An important feature of bioactive glasses, which enables them to work for applications in bone tissue engineering, is their ability to enhance revascularization, osteoblast adhesion, enzyme activity and differentiation of mesenchymal stem cells as well as osteoprogenitor cells. An extensive amount of research work has been carried out to develop silicate, borate/borosilicate bioactive glasses and phosphate glasses. Along with this, some metallic glasses have also been investigated for biomedical and technological applications in tissue engineering. Many trace elements have also been incorporated in the glass network to obtain the desired properties, which have beneficial effects on bone remodeling and/or associated angiogenesis. The motivation of this review is to provide an overview of the general requirements, composition, structure‐property relationship with hydroxyapatite formation and future perspectives of bioglasses.Attention has also been given to developments of metallic glasses and doped bioglasses along with the techniques used for their fabrication. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 254–274, 2014.